2020
DOI: 10.3904/kjm.2020.95.6.387
|View full text |Cite
|
Sign up to set email alerts
|

Difference of Clinical Outcomes According to Left Ventricular Hypertrophy and Its Subtype in Korean Patients with Acute Myocardial Infarction

Abstract: Background/Aims: Left ventricular hypertrophy (LVH) on clinical outcomes in patients with acute myocardial infarction (AMI) is not clear. This study was performed to investigate the effect of abnormal left ventricular geometry on clinical outcomes in Korean patients with AMI.Methods: A total of 852 consecutive patients with AMI were divided into two groups: normal left ventricular geometry (n = 470; 389 males) and LVH (n = 382; 214 males) groups. Major adverse cardiac events (MACEs) were defined as cardiac dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…On the other hand, the term ‘athlete’s heart’ ( George et al, 1991 ) has been used since 1899 as endurance training-type exercises such as triathlon and cycling were known to physiologically induce cardiovascular adaptation and systematic changes in the cardiac structure ( Utomi et al, 2014 ) and produce beneficial changes ( McMullen et al, 2007 ). However, continuous follow-up investigations are needed as it was reported that structural changes in the left ventricle were associated with an increased risk of cardiovascular morbidity and mortality ( Kim et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the term ‘athlete’s heart’ ( George et al, 1991 ) has been used since 1899 as endurance training-type exercises such as triathlon and cycling were known to physiologically induce cardiovascular adaptation and systematic changes in the cardiac structure ( Utomi et al, 2014 ) and produce beneficial changes ( McMullen et al, 2007 ). However, continuous follow-up investigations are needed as it was reported that structural changes in the left ventricle were associated with an increased risk of cardiovascular morbidity and mortality ( Kim et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%